Zakat Management Formulation: Improving the Quality of Management with a Quality Assurance approach - Fasiha, Fasiha; Abdullah, Muh. Ruslan (Technium Social Sciences Journal, 2022)
The rapid growth of zakat institutions in Indonesia is not accompanied by amil zakat’s performance, which has a low impact on realizing the collection and distribution of ZIS funds. Under these conditions, a new formulation is needed in the management of zakat. This paper aims to develop the concept of zakat management with a quality assurance approach. The findings in the study reveal that quality assurance in zakat institutions as a form of the quality system includes standardization of management, as a measure of amil performance, the process is carried out systematically and consistency, quality orientation, has a work culture, there is an increase in the results of zakat management. The concept of quality assurance forms zakat management activities’ functionalization to make it easier for amil and staff to understand zakat management implementation. Besides that, it also forms 1) strengthening zakat management regulations that impact amil compliance in managing zakat and muzakki compliance in paying zakat to BAZNAS, 2) Adopting quality management, which consists of planning, organizing, implementing, and controlling, 3) Quality Assurance leads to the professionalism that pays attention to work processes that are systematic, consistent, and following applicable work procedures and procedures. Thus a management system is formed, an organizational structure effectively and efficiently, a professional amil and staff, a reporting system, a monitoring system, an evaluation system, and a quality assurance system